Substantiation of Price Decisions in a Crisis Context - Vasile DEAC; Mihai VRÎNCUŢ; Oana PĂUN; Irina RAICU (Revista de Management Comparat International)
In this article the authors aim to address key issues regarding pricing decision substantiation in a crisis context and to create an overview of the elements that should underlie such substantiation. We can say that making price decisions is both a science and an art, based on precise calculations and sound economic reasoning. But, especially in a crisis context, such reasoning and calculations should not exclude intuition, flair, hunches, and experience and so on, all instruments belonging to the art of management. A solid reasoning assumes that those involved ask the right questions and understand all the factors that determine the success of some price decisions and failure of others.